Effect of Bacille Calmette–Guérin vaccination on immune responses to SARS‐CoV‐2 and COVID‐19 vaccination - Nicole L Messina; Susie Germano; Amy W Chung; Carolien E van deSandt; Natalie E Stevens; Lilith F Allen; Rhian Bonnici; Julio Croda; Claudio Counoupas; Branka Grubor‐Bauk; Ebene R Haycroft; Katherine Kedzierska; et al. (Clinical & Translational Immunology)
Abstract Objectives Bacille Calmette–Guérin (BCG) vaccination has off‐target effects on disease risk for unrelated infections and immune responses to vaccines. This study aimed to determine the immunomodulatory effects of BCG vaccination on immune responses to vaccines against SARS‐CoV‐2. Methods Blood samples, from a subset of 275 SARS‐CoV‐2‐naïve healthcare workers randomised to BCG vaccination (BCG group) or no BCG vaccination (Control group) in the BRACE trial, were collected before and 28 days after the primary course (two doses) of ChAdOx1‐S (Oxford‐AstraZeneca) or BNT162b2 (Pfizer‐BioNTech) vaccination. SARS‐CoV‐2‐specific antibodies were measured using ELISA and multiplex bead array, whole blood cytokine responses to γ‐irradiated SARS‐CoV‐2 (iSARS) stimulation were measured by multiplex bead array, and SARS‐CoV‐2‐specific T‐cell responses were measured by activation‐induced marker and intracellular cytokine staining assays. Results After randomisation (mean 11 months) but prior to COVID‐19 vaccination, the BCG group had lower cytokine responses to iSARS stimulation than the Control group. After two doses of ChAdOx1‐S, differences in iSARS‐induced cytokine responses between the BCG group and Control group were found for three cytokines (CTACK, TRAIL and VEGF). No differences were found between the groups after BNT162b2 vaccination. There were also no differences between the BCG and Control groups in COVID‐19 vaccine‐induced antigen‐specific antibody responses, T‐cell activation or T‐cell cytokine production. Conclusion BCG vaccination induced a broad and persistent reduction in ex vivo cytokine responses to SARS‐CoV‐2. Following COVID‐19 vaccination, this effect was abrogated, and BCG vaccination did not influence adaptive immune responses to COVID‐19 vaccine antigens.